Impact of Dietary Protein Reduction on Broiler Performance, Carcass Composition, and Meat Quality - Mostafa, Iman; Barari, Mohammad; Asasi , Keramat (Journal of Poultry Sciences and Avian Diseases, 2025)
Protein is a crucial nutrient in poultry nutrition, influencing growth, metabolism, and carcass composition. Optimizing dietary crude protein (CP) levels while ensuring adequate amino acid supplementation is essential for maximizing broiler performance and economic efficiency. This study evaluated the effects of reducing dietary CP levels on broiler growth performance, feed efficiency, carcass composition, and meat quality. A total of 150 one-day-old Ross 308 broilers were randomly assigned to three dietary treatments: low protein (LP), medium protein (MP), and high protein (HP). The LP group received 18%-16%-14% CP, the MP group received 20%-18%-16% CP, and the HP group received 22%-20%-18% CP across different growth phases. Results indicated that the HP group achieved the highest final body weight (2.78 kg), followed by the MP (2.53 kg) and LP (2.29 kg) groups (p<0.05). The Feed Conversion Ratio (FCR) was significantly lower in the LP group, indicating higher feed efficiency, although this was associated with reduced weight gain. The HP group exhibited the highest carcass weight, breast muscle percentage, and protein deposition, whereas the LP group had increased abdominal fat accumulation (p<0.05). Meat quality assessments revealed that the LP group had higher pH values, lower water-holding capacity, and reduced texture and tenderness scores compared to the MP and HP groups. These findings suggest that while reducing dietary CP improves feed efficiency and may reduce nitrogen excretion, excessive reductions negatively impact growth performance, carcass composition, and meat quality. A moderate CP reduction and optimized amino acid supplementation may provide a sustainable strategy for balancing economic feasibility, environmental impact, and broiler productivity.